OPTIMALISASI PERTUMBUHAN DAN KANDUNGAN VITAMIN C KAILAN (Brassica alboglabra L.) MENGGUNAKAN BOKASHI SERTA EKSTRAK TANAMAN TERFERMENTASI - Aulia Rani Annisava (Jurnal Agroteknologi, 2013)
The natural biocontroller such as bokashi and fermented plant extract (FPE) from some plants are the alternatives to substitute fertilizer and pesticide. This biocontroller is really needed in application of sustainable agricultural system. On the other hand, it can produce nutritious food.This research was done in Bokashi Experimental Garden-EM and Biochemist Laboratory FMIPA UNRI Pekanbaru. The method used in this research was randomized complete design, with 7 treatments of giving bokashi and FPE (bokashi + fermented Annona muricataL. extract, bokashi + fermented Andropogon nardus L. extract, bokashi + fermented Ageratum conyzoidesL. extract, bokashi + fermented Ricinus communis. extract, bokashi + fermented of mixing (Annona muricata., Andropogon nardus., Ageratum conyzoides. and Ricinus communis. extract), bokashi without FPE and without giving bokashi or FPE. Each treatment was replicated for three times and every plot consists of 32 plants. The analysis of data was continued with DNMRT 5 %.The results shows that the giving of bokashi and fermented Annona muricata. extract has better influences compared other treatments. It can improve the height of plant, the leaves content, wet weight of plant and increase the vitamin C content. It is also able to minimize the attacks of the phatogen on Brassica alboglabra’s leaves.